The end of the INF Treaty is looming : a new nuclear arms race can still be prevented - Richter, Wolfgang (2019)
Zusammenfassung: President Trump wants to terminate the Intermediate-Range Nuclear Forces (INF) Treaty signed in 1987. Its aim was to end the nuclear deployment race between the US and the then Soviet Union in Europe. Trump justified his intention by accusing Russia of violating the Treaty. Moscow denies this and also accuses Washington of being in breach of the Treaty. Trump has argued that China’s INF potential is also jeopardising the US’s strategic position. However, this unilateral move by Washington contradicts NATO’s recent positions. If the US were to withdraw from the INF Treaty, another cornerstone of the European security order and the global nuclear order would collapse. Unpredictability and destabilisation would increase. Europe must resolutely oppose the threat of a new nuclear arms race. It should insist on verifying the accusations from both sides under transparent and cooperative conditions and, if necessary, agree on additional stabilisation measures in order to preserve the Treaty or limit the consequences of a US withdrawal